ASPHALT EXTRACTION TEST INVESTIGATION: POST AUDIT URGENCY AND THE FOLLOW UPS (CASE STUDY: ROAD SEGMENT MAINTENANCE Ir. SOEKARNO Rd–BATU) - Riandono Pramaputro (Universitas Islam Malang, 2021)
In the most common opinions, the asphalt content test cannot be carried out during the post audit. But there are complaints about the poor quality of hotmix asphalt works in public sector projects from road users. In these cases, auditors must maintain reputation of the Government to accommodate trust in the development that has been done, by carrying out the function of monitoring and evaluating, including in the evaluating of road maintenance work. From visual observations, the the most conditions of routine maintenance work (on the study object) are not good as expected. Also, the test results of the asphalt content in the mixture (extraction) have proven that the quality does not meet the required technical specifications, in where the density value and the mixed asphalt content is 15.24% lower than the allowable tolerance. Under these conditions, auditors can assume that the similarity range of asphalt concrete (AC-WC) quality is still too far from the required specifications. Complaints about the poor quality of hotmix asphalt works must be accommodated by auditors to maintain the image and reputation of the Government in the trust of Regional Development.